A Case Of Esophagitis Cicatricial Accompanied By Pyloric Stenosis Due To Strong Acid Ingestion - Gunawan, Sony; Maimunah, Ummi (Journal of Neonatal Surgery, 2025)
Corrosive chemical ingestion is still a big problem, being the most common cause of toxic exposure, especially in developing and even developed countries. It was reported that a 32-year-old female patient with advanced caustic injury accompanied by moderate-severe dehydration complications due to nausea and vomiting, profuse, malnutrition, anaemia, hypo albumin and electrolyte disorders (hypokalaemia and hyponatremia) with a history of ingestion of corrosive substances with strong acids (toilet cleaning liquid) 10 months ago. The patient underwent endoscopy as a diagnostic and therapeutic procedure, a picture of cervical erosion of the distal oesophagus (zargar degree 2B) was obtained accompanied by a gastric wide cervical injury (zargar degree 3B). Dilatation w / CRE Balooning and installation of NBD as nutrient access was carried out 5 time after a few weeks, but the stricture did not give a good enough response. With this condition, definitive therapeutic action with surgical measures is considered. Clinical and nutritional improvements through the insertion of the NBD tube and the application of the jejunostomy tube before the procedure aim to minimize the risk of complications of operative actions due to anastomosis leakage.